PENEGAKAN HUKUM TINDAK PIDANA PENADAHAN KENDARAAN BERMOTOR HASIL PENCURIAN DI WILAYAH HUKUM KEPOLISIAN SEKTOR KUBU - Nuri Indriyanti; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The criminal act of tribunal shall constitute the act of evil relief or conspiracy as the act is regulated in article 480 of the Criminal Code. The problems that arise in the community, especially in Kubu sub-district of Rokan Hilir Regency are the people of Kubu Sub-district consider that the crime is not a crime but an ordinary thing, it happens because of the lack of awareness and legal compliance of the community, so the action tends to be ignored.The purpose of this thesis writing is: firstly to know the law enforcement of criminal acts of motor vehicle stolen from theft in the jurisdiction of the police sector of the camp, secondly to know what are the obstacles in law enforcement criminal act of stolen motor vehicle stolen in jurisdiction of police sector, and third to determine the right effort to overcome obstacles of criminal law enforcement of motor vehicle stolen results in the jurisdiction of the police sector of the faction. This type of research can be classified in the type of sociological juridical research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under investigation.From the results of research problems there are three main things that can be concluded. First, the enforcement of criminal law on theft of motorized vehicles in the jurisdiction of the Police of the Kubu Sector is conducted based on reports or complaints of the community as victims. Secondly, the obstacles to enforcement of criminal acts of motor vehicle suspension in the jurisdiction of the Police in the Kubu Sector are the social condition of the community, the development of the regional mode by making a considerable distance, the low awareness of community law, the lack of socialization with the community, and the lack of supervision by the enforcement officers law. Third, the efforts made to overcome obstacles in the law enforcement of criminal acts of motor vehicle stolen from theft in the jurisdiction of the Police of Kubu Sector is by reducing the number of motor vehicle theft, while the effort to enforce its law is by socializing or counseling the law and increasing supervision and cooperation between the Police of the Regional Sector on the stolen vehicle rearrangement of theft.